GAFUR GHULAM IS A PATRIOTIC WRITER - Abdusattorov Shohjahon Joʻrabek oʻgʻli (Journal Park Publishing, 2023)
Through this annotation, Gafur Ghulam's works are loved by the majority of readers of Uzbekistan and the world. Gafur Ghulam created a unique style by using the traditional styles of Uzbek literature in a modern style. In his works, he once again proves that he is a writer who loves and honors his nation.
Keywords: Patriotism, writer of the nation, justice, Gafur Ghulam, Shum boy, Great person, writer of the people, poet.